Kesiapan Petani Kelapa Sawit Swadaya dalam Implementasi ISPO: Persoalan Lingkungan Hidup, Legalitas dan Keberlanjutan - Arya Hadi Dharmawan; Fredian Tonny Nasdian; Baba Barus; Rilus A Kinseng; Yoyoh Indaryanti; Hana Indriana; Dyah Ita Mardianingsih; Faris Rahmadian; Hilda Nurul Hidayati; Ade Mirza Roslinawati (School of Postgraduate Studies, Diponegoro Univer, 2019)
The expansion of oil palm plantations run very quickly within two decades in Indonesia. It provides a certain amount of risk against natural resources and the environment. These risks are mainly landscape changes, ecosystems changes and livelihood system change of the rural society. In order to suppress risk, sustainability standards for plantation operation, needs to be implemented. One of the instruments that ensure sustainability standards is ISPO (Indonesia Sustainable Palm Oil). However, its implementation is still limited to be voluntary. In the near future, ISPO will be implemented as mandatory for all business model of oil palm plantation as well as for oil palm mills. This research is about to find out the readiness of the oil palm smallholders to implement ISPO, in particular with regard to the parameters of land seeds legality, land legality, and knowledge on the management of the environment. This research was conducted in several villages in three locations, namely in Riau, Central Kalimantan and East Kalimantan Province. A number of respondents were withdrawn from each village and were selected using simple random sampling method. The results showed that land legality parameter, legality of the seed, and knowledge of oil palm smallholders about environmental management reveals unreadiness of the smallholder to carry out ISPO certification. Thus, the risk of a oil palm plantation expansion towards natural resources and the environment, will still be a great challenge in the future.